City Partnership (Sister City) Between Banda Aceh (The Republic Of Indonesia) And Samarqand (The Republic Of Uzbekistan) On Trade And Industry In Banda Aceh - Istiq Farah Lyndi; M. Putra Iqbal (Jurnal Ilmiah Mahasiswa Bidang Hukum Kenegaraan, 2018)
The Memorandum of Understanding on City Partnership and Cooperation between Banda Aceh (The Republic of Indonesia) and Samarqand (The Republic of Uzbekistan) was established on 2011. Both local government of Banda Aceh and Samarqand agreed on several point including in the Trade and Industry aspect which could support the economic development in Banda Aceh. However, from the preliminary research it is found that there is no implementation on the point on trade and industry of the MOU itself. The focus of this research is to analyze the mechanism of establishing an international cooperation by local government of Aceh and also to analyze the obstacle on the implementation of the mentioned MOU. This research is conducted under juridical empiric method. The data in this study were obtained through both library and field research. The library research is to acquire secondary data by way of studying the legislation, books, the internet and other scholarly works related to the problems of the research and fieldwork conducted for obtaining primary data by interviewing respondents or informants. The mechanism of establishment of the MOU on city partnership between Banda Aceh and Samarqand has fulfilled the Law No. 24 of 2000 on Treaty and the Ministry of Foreign Affair Regulation No: 09/A/KP/XII/2006/01. Meanwhile, the implementation of the point of the MOU itself could not be accomplished because of the absence of the Joint Working group, the lack of financial availability, and also the lack of communication and coordination between both local governments. Further, lack of coordination between the local government of Banda Aceh and Indonesia Ministry of Foreign Affair affects the implementation as well. In order to have successful MOU in the future, local government should be more well prepared such as establish the Join working group, preparing the certain budget for conducting the international cooperation, increasing the human resources especially in the field of foreign language to facilitate the communication. As the coordinator and supervisor of the international cooperation, the Ministry of Foreign Affair should do evaluation of the implementation of the international cooperation annually so that the local government might get the solution of the problem which is faced when the implementation.